Avoidance and treatment of muscle soreness (IAAF @-Letter for CECS Level II Coaches, 2004)
Muscle soreness is an unavoidable side effect of hard training. The only way to avoid post-exercise muscle soreness completely is to avoid exercise. However, according to the available advisory literature, there are several things one can do to minimize muscle soreness - caused mainly by damage to muscle proteins - without sacrificing fitness. Common tips are the following (Quinn, 2004): • Warm up thoroughly before activity. • Cool down completely after exercise. • Perform easy stretching before training. • Perform thorough flexibility exercises after training, while the muscles are warm. • Start with easy to moderate activity and build up your intensity over time. • Avoid making sudden major changes in the type of exercise you do and in the amount of time that you exercise. Other typical recommendations for treatment include topical application of athletic balms, creams, and/or ice, submersion in hot baths, exposure to a sauna, and the use of aspirin or other anti-inflammatory drugs (Clarkson, 1996). A lot of research has been done to examine the effects of these measures.